Pengaruh Pendidikan Etika Bisnis dan Gender Terhadap Persepsi Etis Mahasiswa Akuntansi Politeknik Negeri Padang - Kinda Dania; Ulfi Maryati; Armel Yentifa (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This study aims to determine the effect of business ethics education and gender on the ethical perception of Accounting students at Politeknik Negeri Padang. The samples in this study are Diploma IV students majoring in Accounting from the class of 2019 and Student of Continuing Diploma IV from the class of 2021-2023 who have taken professional business ethics and auditing education courses. The sampling method used purposive sampling. Data were calculated using the slovin formula and then obtained as many as 85 students based on criteria. Data collection used distributing questionnaires with Google Forms. Data were analyzed using multiple linear regression analysis using SPSS. The test results showed the business ethics education variables do not effect on the ethical perception of accounting students, while the gender variables have a positive and significant effect on the ethical perception of accounting students.